Mutational changes in the hemagglutinin of equine H3 influenza viruses result in the introduction of a glycosylation site which enhances the infectivity of the viruses - Adeyefa, C A; McCauley, J W; Tomori, O (Folia microbiologica, 1997)
The complete amino acid sequences of the hemagglutinin (HA) glycoprotein of three equine-2 influenza viruses from tropical Africa are presented in comparison with that of a well characterized European equine-2 virus (Suffolk/89) and a consensus sequence from the database. The sequences of the tropical African viruses were deduced from the complete nucleotide sequences of their HA genes reported earlier. Mutational changes in the nucleotide sequences resulted in amino acid changes in the HA which led to the introduction of a new asparagine-linked (N-linked) glycosylation site in two viruses. This new glycosylation site enhanced the infectivity of these viruses as investigated by plaque assay, virus titration in embryonated chicken eggs and tunicamycin treatment. The role of N-linked glycosylation of influenza virus HA glycoprotein in virus infectivity, antigenicity and immunogenicity is discussed in the light of the results of our previous and present investigations.
Keywords: Chick Embryo; Nigeria; Animals; Virulence; posttranslační úpravy proteinů; Cytopathogenic Effect, Viral; sekvenční homologie aminokyselin; Sequence Homology, Amino Acid; Glycosylation; sekvence aminokyselin; Tunicamycin; Molecular Sequence Data; Protein Processing, Post-Translational; hemaglutininové glykoproteiny viru chřipky; Amino Acid Sequence; kultivované buňky; Hemagglutinin Glycoproteins, Influenza Virus; cytopatogenní efekt virový; virus chřipky A; Influenza A virus; virulence; Cells, Cultured; asparagin; molekulární sekvence - údaje; konsenzuální sekvence; Sequence Alignment; Consensus Sequence; glykosylace; Nigérie; zvířata; Asparagine; tunikamycin; sekvenční seřazení; kuřecí embryo